Striatal insights: a cellular and molecular perspective on repetitive behaviors in pathology - Burton, Charlotte Lauren; Longaretti, Alessandra; Zlatanovic, Andjela; Gomes, Guilherme Monteiro; Tonini, Raffaella (Frontiers in Cellular Neuroscience, 2024)
Animals often behave repetitively and predictably. These repetitive behaviors can have a component that is learned and ingrained as habits, which can be evolutionarily advantageous as they reduce cognitive load and the expenditure of attentional resources. Repetitive behaviors can also be conscious and deliberate, and may occur in the absence of habit formation, typically when they are a feature of normal development in children, or neuropsychiatric disorders. They can be considered pathological when they interfere with social relationships and daily activities. For instance, people affected by obsessive-compulsive disorder, autism spectrum disorder, Huntington's disease and Gilles de la Tourette syndrome can display a wide range of symptoms like compulsive, stereotyped and ritualistic behaviors. The striatum nucleus of the basal ganglia is proposed to act as a master regulator of these repetitive behaviors through its circuit connections with sensorimotor, associative, and limbic areas of the cortex. However, the precise mechanisms within the striatum, detailing its compartmental organization, cellular specificity, and the intricacies of its downstream connections, remain an area of active research. In this review, we summarize evidence across multiple scales, including circuit-level, cellular, and molecular dimensions, to elucidate the striatal mechanisms underpinning repetitive behaviors and offer perspectives on the implicated disorders. We consider the close relationship between behavioral output and transcriptional changes, and thereby structural and circuit alterations, including those occurring through epigenetic processes.